CLUSTER ANALYSIS CHARACTERIZATION OF RESEARCH TRENDS CONNECTING SOCIAL MEDIA TO LEARNING IN THE UNITED KINGDOM - Pereira, Ana Lucia; Costa, Cristina; Lunardi, Jose Tadeu (Revista de Produtos Educacionais e Pesquisas em Ensino, 2017)
In this work we present a characterization of and discuss the research trends connecting social media to learning in the United Kingdom in the last six years. The data set for this research comprises articles published in educational journals indexed in the Web of Science® database. A cluster analysis was used to group similar articles in the data set. We characterized the main research trends by identifying the typical features of the articles within each of the main groups that emerged from this analysis.